Equipping Students and Beyond with Sound COVID‐19 Knowledge to Survive and Thrive Despite the Pandemic. Issue 1 (14th October 2022) - Chan, Helen; Chu, Sam; Gala, Bhakti; Islam, Md. Anwarul; Batool, Syeda Hina; Bhardwaj, Raj Kumar; Lamba, Manika; Jayasekara, Prasadi Kanchana
ABSTRACT: The COVID‐19 pandemic necessitated the understanding of the infodemic for making informed decisions. Limiting the spread of health misinformation and disinformation was the primary goal of the health informatics project. The project became the recipient of the ASIS&T "Chapter Innovation of the Year Award 2021". A repertoire of online and offline initiatives was carried out with 9 well‐researched videos for promoting health informatics. Since August 2021, thousands of academics, librarians, teachers, parents, and students from 16 countries and regions were invited to be science communicators to create and disseminate accurate health information in their areas through an international digital story writing competition. In this paper, we will discuss the strategies of responding to the information crisis, including employing interventions that protect against the infodemic and mitigate its harmful effects, to strengthen the resilience of individuals and communities in dealing with it in an information‐resilient society.